Patterns of lichen richness across elevation in the Manaslu Conservation Area, central Nepal - Baniya, Chitra Bahadur; Shrestha, Krishna Kumar; Chongbang, Til Bikram (Nepal Journal of Botany, 2024)
This study investigates the distribution of lichen richness along elevation gradients in the Manaslu Conservation Area, Central Nepal. A total of 95 lichen species, belonging to 40 genera and 18 families were recorded. The dominant growth forms were foliose, fruticose, crustose, and squamulose. Corticolous lichens were the most prevalent, followed by saxicolous, terricolous, and muscicolous species. Among the families, Parmeliaceae exhibited the highest species diversity, followed by Cladoniaceae. A hump-shaped relationship between elevation and lichen species richness was observed, with the peak occurring at approximately 3000 meters in the Manaslu Conservation Area. This pattern aligns with similar findings in other mountainous regions worldwide, indicating optimal growth conditions in the mid-elevation range. Contrasting lichen richness patterns with other regions in Nepal underscored the influence of broader environmental factors. The dominance of the Parmeliaceae and Cladoniaceae families highlights their ecological importance in shaping the lichen community structure. These findings have implications for lichen conservation and management strategies. Preserving the unique environmental conditions and microhabitats within the peak elevation range is crucial for maintaining lichen diversity. Further research is necessary to comprehend the underlying ecological processes and guide targeted conservation efforts.